3-coloring triangle-free planar graphs with a precolored 9-cycle. (February 2018) - Choi, Ilkyoo; Ekstein, Jan; Holub, Přemysl; Lidický, Bernard
Abstract: Given a triangle-free planar graph G and a 9 -cycle C in G, we characterize situations where a 3 -coloring of C does not extend to a proper 3 -coloring of G . This extends previous results when C is a cycle of length at most 8 .